2010
DOI: 10.1080/15374416.2010.501291
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Trauma-Focused CBT With Fidelity and Flexibility: A Family Case Study

Abstract: Effective approaches for the treatment of childhood posttraumatic stress disorder and traumatic grief are needed given the prevalence of trauma and its impact on children's lives. To effectively treat posttraumatic stress disorder in children, evidence-based practices should be implemented with flexibility and responsiveness to culture, developmental level, and the specific needs of the family. This case study illustrates flexibility with fidelity in the use of a manualized treatment, describing the implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In turn, reexperiencing might be best addressed through interventions such as cognitive processing, which help youth to work through the underlying emotions and thoughts that are keeping the youth "stuck" in the trauma, including ruminative worrying, self-blame, or revenge fantasies. Modularized approaches to child trauma treatment such as Trauma-Focused CBT (Cohen et al, 2006) have the advantage of including each of these components in the treatment manual and encouraging the clinician to flexibly adapt implementation to the specific needs of the client (Kerig, Sink, Cuellar, Vanderzee, & Elfstrom, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, reexperiencing might be best addressed through interventions such as cognitive processing, which help youth to work through the underlying emotions and thoughts that are keeping the youth "stuck" in the trauma, including ruminative worrying, self-blame, or revenge fantasies. Modularized approaches to child trauma treatment such as Trauma-Focused CBT (Cohen et al, 2006) have the advantage of including each of these components in the treatment manual and encouraging the clinician to flexibly adapt implementation to the specific needs of the client (Kerig, Sink, Cuellar, Vanderzee, & Elfstrom, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive behavioural therapy (CBT) and trauma-focused cognitive behavioural therapy (TF-CBT) are evidencebased practices that have components well suited to a strengths-based framework. Kerig, Sink, Cuellar, Vanderzee, and Elfstrom (2010) note that the TF-CBT principles include a focus on the provider using a strengths-based approach to further clients' self-efficacy. Randomised controlled trials of TF-CBT have found treatment gains for children at the conclusion of the intervention and at follow-up (Cohen et al, 2010), including for children who have experienced child sexual abuse (Deblinger, Mannarino, Cohen, Runyon, & Steer, 2011;Deblinger, Mannarino, Cohen, & Steer, 2006).…”
Section: Strengths-based Interventionsmentioning
confidence: 99%
“…CBT and TF-CBT interventions include a strengthsbased approach (Kerig et al, 2010) that was consistent with The Home's framework. Additionally, many agency staff had previously been using a variety of other strengths-based tools, such as therapeutic crisis intervention (TCI), skills-based training, SFT, and relaxation techniques in their work with children and youth.…”
Section: Overview Of the Strengths-based Practice Frameworkmentioning
confidence: 99%
“…When the disruptions and stress imposed by acculturation are managed effectively, such as when Latinx parents maintain active involvement in their child's activities, fewer acculturation-based behavioral problems occur [97,98]. These are skills that can be taught, albeit only within programs that are grounded in their developmental and cultural experiences [99].…”
Section: Addressing Substance Use and Unhealthy Diet Behaviors In Latinx Adolescents From An Ecodevelopmental Frameworkmentioning
confidence: 99%